(3GdCSS GdYdejI aj GdbjGS GdeMGSHjs - (3gGOj QVG(B, (3GdUaGQs ((3YeGf(B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2006)
(3fThA GdeMGSHI hJWhQgG, GdfXGe GdeMGSHj hGdOhQI GdeMGSHjI, GdYedjGJ GdJehjdjI, GdYedjGJ GdEjQGOjI, GdYedjGJ GdQCSeGdjI, aJQI GdMSGHGJ GdNJGejIs
(3HHdjhZQGajG(B: (3U(B.397s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeMGSHIs